Spatiotemporal analysis of psychoactive drug consumption in Brazil during the COVID-19 pandemic - Evani Leite de Freitas; Rafael Santos Erbisti; Branca Grinberg-Weller; Daniel Claudiano Cabral Pinto; Elaine Silva Miranda (PLoS ONE, 2026)
The COVID-19 pandemic had a significant impact on Brazil, although its effects were not homogeneous across the country. Socioeconomic disparities may influence epidemiological patterns during health emergencies, which impact population mental health. This study aimed to analyze the consumption of psychoactive medicines during the COVID-19 pandemic in Brazil and to characterize its spatiotemporal dynamics, identifying associated social, economic, and demographic factors. We used publicly available retail pharmacies dispensing data from January 2018 to September 2021 across Brazil’s municipalities. A statistical model was developed based on indicators of infrastructure, human capital, and labor and income. Generalized additive models were used to characterize the spatiotemporal distribution of drug consumption. In September 2021, average consumption in municipalities reporting COVID-19–related deaths was 22% higher than in municipalities with no reported deaths. Among the most frequently consumed medicines during the study period, second-generation antidepressants were predominant. Life expectancy, employment and education showed positive linear associations with consumption, whereas inadequate water supply and sanitation were inversely associated. Municipality income was positively associated with average consumption of psychoactive medicines, but those with a very high-income development index showed more complex dynamics. Our results suggest that COVID-19 mortality was associated with psychotropic medicines consumption and indicate the need to address socioeconomic vulnerability as a key component of public health emergency response. The COVID-19 pandemic had a significant impact on Brazil, although its effects were not homogeneous across the country. Socioeconomic disparities may influence epidemiological patterns during health emergencies, impacting population mental health. This study aimed to analyze the consumption of psychoactive medicines during the COVID-19 pandemic in Brazil and to characterize its spatiotemporal dynamics, identifying associated social, economic, and demographic factors. We used publicly available data from retail pharmacy dispensing from January 2018 to September 2021 across Brazilian municipalities. A statistical model was developed based on indicators of infrastructure, human capital, labor, and income. Generalized additive models were used to characterize the spatiotemporal distribution of drug consumption. In September 2021, average consumption in municipalities reporting COVID-19–related deaths was 22% higher than in municipalities with no reported deaths. Among the most frequently consumed medicines during the study period, second-generation antidepressants were predominant. Life expectancy, employment, and education showed positive linear associations with consumption, whereas inadequate water supply and sanitation were inversely associated. Municipality income was positively associated with the average consumption of psychoactive medicines, but those with a very high human development index for income showed more complex dynamics. Our results suggest that COVID-19 mortality was associated with psychotropic medicine consumption and indicate the need to address socioeconomic vulnerability as a key component of public health emergency responses.